Visual fatigue effects on vergence dynamics in asymptomatic individuals. (22nd August 2013) - Thiagarajan, Preethi; Ciuffreda, Kenneth J
Abstract Purpose To evaluate objectively changes in vergence dynamics following intentional visual fatiguing tasks using congruent (C) and non‐congruent (NC) vergence stimulus demands. Methods Pre‐ and post‐task vergence dynamics to a 10.3° disparity stimulus were recorded objectively in 12 adult, asymptomatic individuals for both convergence and divergence. There were two fatigue‐inducing tasks: Congruent or C‐task: Subjects altered bifixation (50 cycles) between reduced Snellen charts at 2 m and at 20 cm every 3 s. Non‐congruent or NC task: Subjects performed 50 cycles of vergence flipper (7Δ BO/BI), while bifixating a reduced Snellen chart at 40 cm. Pre‐ and post‐task mean amplitude, time constant, peak velocity, and steady‐state response variability were compared. Results There was a significant increase in mean post‐task, steady‐state response variability for both the C and NC tasks. However, there were no significant group differences for either convergence or divergence between the pre‐ and post‐mean amplitude, time constant, and peak velocity parameters for both the C and NC tasks, although post‐task peak velocity was consistently reduced. Conclusions Steady‐state vergence response variability was found to be the critical objective parameter to demonstrate significant fatigue effects in the group. Peak velocity was also consistently reduced to a small extent in the NC task. We speculate that these fatigue effects are of a central, and not of peripheral, origin.